2022
DOI: 10.4142/jvs.22001
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ladder-shape melting temperature isothermal amplification (LMTIA) assay for detection of African swine fever virus (ASFV)

Abstract: Background Due to the unavailability of an effective vaccine or antiviral drug against the African swine fever virus (ASFV), rapid diagnosis methods are needed to prevent highly contagious African swine fever. Objectives The objective of this study was to establish the ladder-shape melting temperature isothermal amplification (LMTIA) assay for the detection of ASFV. Methods LMTIA primers were designed with the p72 gene of ASFV as the target, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[ 30,47 ] The DNA fragments were obtained by digestion with EcoRI and used directly for the assay. [ 48 ] PAGE analysis confirmed that the prepared DNA fragments for each target gene hybridized with the corresponding probe DNA, and the amplified products were obtained after performing HCR (Figure S11a,b, Supporting Information). Additionally, the probe and helper DNA specific to the B646L gene generated amplicons only for the B646L gene target, implying that our HCR hairpins were highly specific to each target (Figure S11c, Supporting Information).…”
Section: Resultsmentioning
confidence: 76%
“…[ 30,47 ] The DNA fragments were obtained by digestion with EcoRI and used directly for the assay. [ 48 ] PAGE analysis confirmed that the prepared DNA fragments for each target gene hybridized with the corresponding probe DNA, and the amplified products were obtained after performing HCR (Figure S11a,b, Supporting Information). Additionally, the probe and helper DNA specific to the B646L gene generated amplicons only for the B646L gene target, implying that our HCR hairpins were highly specific to each target (Figure S11c, Supporting Information).…”
Section: Resultsmentioning
confidence: 76%
“…Wang et al has devised a ladder-shaped melting temperature isothermal amplification (LMTIA) technique that specifically targets the ASFV-B646L gene. This method exhibits the same sensitivity of commercially available qPCR reagent kits with a LOD of 0.5 copies/μL (119). Furthermore, the integration of LAMP with carbon nanodots (CND) technology has facilitated the development of a fluorescent biosensor, enabling the highly sensitive detection of ASFV with a detection sensitivity of 15.21 copies/μL (65).…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 96%
“…Compared to traditional PCR, LMTIA offers several advantages: (1) it does not rely on expensive PCR or qPCR instruments, employing isothermal amplification; (2) rapid reaction, with each reaction taking only 30 min; (3) suitable for shorter target sequences, requiring a minimum length of 60 bp for amplification; (4) high sensitivity, with studies showing 50 times higher sensitivity compared to Loop-mediated isothermal amplification (LAMP) technology [9]; and (5) broad applicability, as the employed Bst enzyme possesses reverse transcriptase activity, making it suitable for various nucleic acid sequences, including RNA. This technique has been successfully applied in diverse fields, such as the rapid detection of cassava components in sweet potato starch [10] and African swine fever virus detection [11].…”
Section: Introductionmentioning
confidence: 99%